Tracking And Health Monitoring System Of Soldier - Chethan Kodidala, Yagnasree Devathi, Navya Mekala, HemaDurga Dommala, Prof. Jyothy S T (International Journal of Advanced Science and Technology, 2020)
Wellbeing and security of the country relies upon the arm powers. Each country has arm power administrations like naval force, armed force and flying corps. Soldier is the foundation of nation's arm powers. Soldiers play an important role. But sometimes they will lose their lives in battle because of absence of medical help at required time and lack communication with the authorities. So, we designed a framework which can help a soldier based on the health status and help needed by the soldier. The framework is for soldier security and safety. In this framework, smart sensors are attached to the body of warriors. The pulse sensor and temperature sensor output values are recorded continuously through the cloud to store the data and for analyse of soldier’s health through graphs in ThingSpeak software and when sensor output values reaches the critical values then data of the soldier like location, health condition sent directly to the officials to the since each soldier  has a GSM module which enables the communication with the basestation. The GPS (Global Positioning System) gives the location of a soldier by providing latitude and longitude values. By integrating all these into single unit, we built up the fundamental guarding framework which is light weighted and compact system.